1981
DOI: 10.1103/physrevlett.47.1110
|View full text |Cite
|
Sign up to set email alerts
|

Λ-Nuclear Properties from the Spectroscopy ofCΛ13

Abstract: A comprehensive shell model for light hypernuclei has been developed and applied to AC. Absolutely normalized distorted-wave calculations yield angular distributions in excellent agreement with experiment, allowing spin assignments to be made. Coherences arising from the distinguishability of the A are predicted theoretically and observed in the data. The overall comparison with experiment places constraints on residual interaction matrix elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…A later theoretical calculation gave weaker constraint [13]. A small splitting was also indicated by the 13 C͑K 2 , p 2 ͒ 13 L C reaction and 0.36 6 0.3 MeV was obtained [5,14]. Hypernuclear g rays observed in 9 L Be indicated that the 3͞2 1 and 5͞2 1 states, which have [͑s 1͞2 ͒ L , 2 1 ͑ 8 Be͒] configuration, are too close to be separated by NaI detectors suggesting small ᐉs splitting [6].…”
Section: (Received 1 September 2000)mentioning
confidence: 97%
“…A later theoretical calculation gave weaker constraint [13]. A small splitting was also indicated by the 13 C͑K 2 , p 2 ͒ 13 L C reaction and 0.36 6 0.3 MeV was obtained [5,14]. Hypernuclear g rays observed in 9 L Be indicated that the 3͞2 1 and 5͞2 1 states, which have [͑s 1͞2 ͒ L , 2 1 ͑ 8 Be͒] configuration, are too close to be separated by NaI detectors suggesting small ᐉs splitting [6].…”
Section: (Received 1 September 2000)mentioning
confidence: 97%
“…However, the relative s-wave and pwave central matrix elements no longer appear in a fixed combination. Here, the choice of the odd-state central interactions is influenced by data on 13 Λ C [7,25]. The resulting energy spectra, dominant components of the wave functions, and calculated cross sections are shown in Table I.…”
mentioning
confidence: 99%
“…PACS numbers: 21.80.+a, 25.30.Rw, 21.60.Cs, 24.50.+g Hypernuclear spectroscopy is a powerful tool for studying the ΛN interaction (N = p, n) given that very limited information can be obtained from Y p (Y = Λ, Σ − , Σ + ) elastic scattering and charge-exchange data [1].…”
mentioning
confidence: 99%
“…lb). It is anticipated [15] that the first state has the radiative width only, whereas the second one decays via the A-hyperon emission. It means that the height of the first peak in EF has to be much higher compared with the second one when the AN-interaction is neglected.…”
Section: Relationship Of the Hypernuclear Excitation Functions To Spementioning
confidence: 99%
“…The disagreement with experiment is indeed removed by including the AN-interaction (see Ref. [15]). It is thus desirable to specify the energy position and to get direct evidence for y-decay of the first resonance in 1A3C.…”
Section: Relationship Of the Hypernuclear Excitation Functions To Spementioning
confidence: 99%